(untitled) (Global Journal of Medical Research, 1970)
Introduction IgA nephropathy an indirect immune-mediated kidney disease is considered the main etiology of glomerulopathies and is also responsible for a large partofall cases of end-stage chronic kidney disease Objective To report the case of a patient admitted to a hospital with clinical presentation of mixed syndrome and presence of vasculitis in the lowerlimbs with a diagnostic hypothesis of IgA nephropathy Methodology The information was obtained by reviewing the chart photographing the diagnostic methods to which the patient was submitted and reviewing the literature Discussion Studies point to the pathogenic mechanism from the deposition of circulating immune complexes in the renal glomerulus leading to inflammation and activation of the immune system The clinical presentationis variable with the mixed syndrome being the most frequent